MODERNISASI LEMBAGA PENDIDIKAN ISLAM - Dede Rubai Misbahul Alam; Muhammad Safiih (STKIP Subang, 2026)
The modernization of Islamic educational institutions is an inevitability in responding to contemporary challenges and competition with general educational institutions. This research aims to describe the concept of modernization of Islamic education in Indonesia, the background of the need for reform, and its historical dynamics over time. The research method used is library research with a descriptive-analytical approach. The results indicate that the modernization of Islamic education in Indonesia involves transformations in the aspects of goals, curriculum, educators, and students. Historically, this modernization was triggered by responses to colonial policies and continued to evolve until the reformation era through the strengthening of the Islamic education system within the national education system. These modernization efforts are carried out to improve the quality of Islamic education so that it remains relevant to developments in science and technology without abandoning its religious values.